2019
DOI: 10.3390/catal9110940
|View full text |Cite
|
Sign up to set email alerts
|

Size-Controlled Synthesis of Pt Particles on TiO2 Surface: Physicochemical Characteristic and Photocatalytic Activity

Abstract: Different TiO2 photocatalysts, i.e., commercial samples (ST-01 and P25 with minority of rutile phase), nanotubes, well-crystallized faceted particles of decahedral shape and mesoporous spheres, were used as supports for deposition of Pt nanoparticles (NPs). Size-controlled Pt NPs embedded in TiO2 were successfully prepared by microemulsion and wet-impregnation methods. Obtained photocatalysts were characterized using XRD, TEM, X-ray photoelectron spectroscopy (XPS), Brunauer–Emmett–Teller (BET) specific surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Degradation of phenol under UV-visible illumination was shown to depend on Pt particle size. Optimum particle size and maximization of activity was achieved using the microemulsion method [ 139 ]. Interestingly, Pt can be deposited over anatase TiO 2 selectively over specific surface planes (like (101)), favoring specific reactions like hydrogen production [ 140 ].…”
Section: Composite Photocatalystsmentioning
confidence: 99%
“…Degradation of phenol under UV-visible illumination was shown to depend on Pt particle size. Optimum particle size and maximization of activity was achieved using the microemulsion method [ 139 ]. Interestingly, Pt can be deposited over anatase TiO 2 selectively over specific surface planes (like (101)), favoring specific reactions like hydrogen production [ 140 ].…”
Section: Composite Photocatalystsmentioning
confidence: 99%
“…The selective deposition of Pt NPs is also attributed to adsorption behavior of the metal precursors on different crystal facets. The uniform deposition of Pt on {101} facets by chemical reduction of H 2 PtCl 6 precursor (different than that for Pt(NH 3 ) 4 Cl 2 ) might be explained by the good adsorption of PtCl [92]. The selective deposition of Pt NPs on DAP results from the fact that the surface of {101} facets is electron-rich, whereas the oxidized {001} surface is electron-deficient.…”
Section: Faceted Semiconductors As Supports For Noble Metalsmentioning
confidence: 98%
“…In contrast to OAP and commercial titania samples modified with noble metals by photodeposition, it has been found that a decrease in the size of Pt NPs results in activity enhancement under both UV and vis irradiation. [92]. The selective deposition of Pt NPs on DAP results from the fact that the surface of {101} facets is electron-rich, whereas the oxidized {001} surface is electron-deficient.…”
Section: Faceted Semiconductors As Supports For Noble Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of ZnO, the surfactants-assisted synthesis allows us to obtain a 3D hierarchical structure. Many researchers [37,38] are working on the formation of new structures of well-known oxide materials due to the appropriate exposition of the crystal facets, e.g., in titania Based on the TEM image obtained for the reference sample (TiO 2 ), it should be noted particles with a rod-like shape were observed. Moreover, the particles are characterized by a diameter of approximately 50 nm and length of 150 nm.…”
Section: Morphologymentioning
confidence: 99%